Immunohistochemical Expression of Dual-Specificity Protein Phosphatase 4 in Patients with Colorectal Adenocarcinoma. (21st January 2015) - Sim, Jongmin; Yi, Kijong; Kim, Hyunsung; Ahn, Hyein; Chung, Yumin; Rehman, Abdul; Jang, Se Min; Lee, Kang Hong; Jang, Kiseok; Paik, Seung Sam
Abstract : The role of dual-specificity protein phosphatase 4 (DUSP4) appears to vary with the type of malignant tumors and is still controversial. The purpose of our study was to clarify the exact role of DUSP4 expression in colorectal adenocarcinoma. We constructed tissue microarrays and investigated DUSP4 expression by immunohistochemistry. DUSP4 was more frequently expressed in adenocarcinomas and lymph node/distant metastases compared to that in normal colorectal tissues and tubular adenomas (P < 0.001 ). Mean DUSP4 expression score was significantly higher in malignant tumors than in benign lesions (P < 0.001 ). DUSP4 expression was significantly correlated with older age (P = 0.017 ), male gender (P = 0.036 ), larger tumor size (P = 0.014 ), nonmucinous tumor type (P = 0.023 ), and higher T stage (P = 0.040 ). Kaplan-Meier survival curves revealed a significant effect of DUSP4 expression on both overall survival and disease-free survival in AJCC stage I (P = 0.008 and P = 0.003, resp., log-rank test) and male gender (P = 0.017 and P = 0.049, resp., log-rank test). DUSP4 protein is frequently upregulated in colorectal adenocarcinoma and may play an important role in carcinogenesis and cancer progression and may be a marker of adverse prognosis.